Performance Models for Perfect and Imperfect Clocks on Timestamp Ordering in Distributed Databases - Christos Bouras; Paul Spirakis (MASCOTS'93, San Diego, California, USA, 1993)
This work presents a model of a distributed database system which provides the framework to study the performance of timestamp ordering concurrency control. We exhibit an analytical solution, which has been tested with extensive simulation. The accuracy seems to be very high. We assume perfect and also imperfect clocks for synchronization and quantify the way in which local clock inaccuracies affect the phenomenon of transaction conflicts.